Measuring the Use of Social Media Networks (SMNs) in Knowledge Sharing, by Using Social Cognitive Theory (SCT) A Study Conducted in Some of Iraqi Universities - Abed Jader, Ahmed Muyasser (Journal of Economics and Administrative Sciences, 2021)
SMNs like Facebook, YouTube, Twitter, WhatsApp,..etc. are among the most popular sites on the Internet. These sites can provide a powerful means of sharing, organizing, finding information and knowledge. The popularity of these sites provides an opportunity to measure the use them in knowledge sharing, which needs a special scale, but unfortunately, there is no special scale for that. Thus, this study supposes to use SCT as a scale to measure the use of SMNs in electronic knowledge sharing due to it has been used to measure knowledge sharing with its traditional form. This study can help the decision-makers to use these SMNs to share the academics’ knowledge in educational institutes to the communities by adopting special plans and strategies to address the main factors in such cases that will help to increase the knowledge sharing between academics and communities.  The aim of this study to know the amount of using SMNs by academics to share their own knowledge with the community, which will reflect on educating the community and disseminate the culture within the community. Additionally, to address what the main factor can affect them to share their knowledge with others. The study uses SCT which consists of three factors: (Personal, Environment, and Behavior) as an independent variable, while the dependent variable is: (Knowledge Sharing). Furthermore, the quantitative method is adopted in this study by using an electronic questionnaire through Google Documents with “Five Scale of Likert” to collect the data from participants (250), who are the staff of some Iraqi universities. SPSS has been used in analyzing the collected data. The findings of the study come up with the following: the environmental factor has the greatest influence, then the behavioural factor which is lesser and the personal factor has the lowest influence. Finally, the study found that there is a possibility and ability to measure knowledge sharing by using SCT electronically.  Paper type: research paper.